LaTeX graphics with TikZ : a practitioner's guide to draw 2D and 3D images, diagrams, charts, and plots in LaTeX using TikZ /: a practitioner's guide to draw 2D and 3D images, diagrams, charts, and plots in LaTeX using TikZ. (2023) - Kottwitz, Stefan
No abstract available